2021
DOI: 10.1016/j.crtox.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The low doses of SWCNTs affect the expression of proliferation and apoptosis related genes in normal human astrocytes

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…It has been shown that very low quantities of SWCNTs may significantly disturb the expression of microRNAs, which participate in the post-transcriptional regulation of most mRNAs and regulate variable physiological and pathophysiological processes in different cells and tissues, including brain tissue (Schratt et al 2006;Agarwal et al 2015;Matamala et al 2018;Wang et al 2018;Goldewski et al 2019;Krichevsky et al 2019;Ma et al 2019;Brennan and Henshall 2020). Previously we have shown that SWCNTs affect the expression of genes encoding enzymes and factors related to immune response, cell proliferation, and cell cycle control as well as some microRNAs in U87 glioma cells and normal human astrocytes (Minchenko et al 2016(Minchenko et al , 2018Rudnytska et al 2021). The present study indicates that SWCNTs at very low quantities significantly down-regulate the expression of numerous microRNAs in the zebrafish embryos in dose-and time-dependent manners.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…It has been shown that very low quantities of SWCNTs may significantly disturb the expression of microRNAs, which participate in the post-transcriptional regulation of most mRNAs and regulate variable physiological and pathophysiological processes in different cells and tissues, including brain tissue (Schratt et al 2006;Agarwal et al 2015;Matamala et al 2018;Wang et al 2018;Goldewski et al 2019;Krichevsky et al 2019;Ma et al 2019;Brennan and Henshall 2020). Previously we have shown that SWCNTs affect the expression of genes encoding enzymes and factors related to immune response, cell proliferation, and cell cycle control as well as some microRNAs in U87 glioma cells and normal human astrocytes (Minchenko et al 2016(Minchenko et al , 2018Rudnytska et al 2021). The present study indicates that SWCNTs at very low quantities significantly down-regulate the expression of numerous microRNAs in the zebrafish embryos in dose-and time-dependent manners.…”
Section: Discussionmentioning
confidence: 96%
“…RNA extraction and cDNA synthesis. Total RNA was extracted from the zebrafish embryos using TRIZOL reagent as described previously (Auf et al 2013;Rudnytska et al 2021). The RNA pellets were washed with 75% ethanol and dissolved in the nuclease-free water.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations